Medico-ethnobiology in Rai Community: A Case Study from Baikunthe Village Development Committee, Bhojpur, Eastern Nepal - Rai, Rabina; Singh, N.B. (Journal of Institute of Science and Technology, 2015)
This paper tried to explore the uses of medicinal animals and plants for the treatment of different diseases in the Rai community of Baikunthe VDC, Bhojpur, Nepal. About 87 plant species belonging to 55 families were used in treating 65 types of diseases while 27 different animal species belonging to 23 families were used in healing 28 ailments. The community is rich in traditional medicinal knowledge and has been using several plants and animal species for healing ailments in their day to day life. Finally, to protect their knowledge, awareness dissemination and further documentation has become vital. Journal of Institute of Science and Technology, 2015, 20(1): 127-132